2005
DOI: 10.2176/nmc.45.156
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cerebral Angiitis Containing Marked Xanthoma Cells With Massive Intraparenchymal Involvement-Case Report-

Abstract: A 27-year-old woman was referred to our hospital with mild disorientation, bilateral abducens nerve palsy, and mild left hemiparesis. Magnetic resonance (MR) imaging revealed diffuse mass lesions resembling malignant glioma in the right frontal intraparenchymal region, with enhancement of multiple meningeal and intraparenchymal nodules. Partial resection of the frontal lesion was performed. Histological examination revealed that the specimens consisted of brain tissue, with marked perivascular infiltration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The present patient had a single, tumor-like enhancing lesion associated with extensive vasogenic edema on MR imaging. Conversely, PACNS presenting multiple lesions that also mimic aggressive multifocal cerebral neoplasm have been reported (26, 3134). A retrospective study of 10 tumor-like PACNS cases in France found that the number of patients with single and multiple lesions was similar (4 and 3 patients, respectively) (35).…”
Section: Discussionmentioning
confidence: 99%
“…The present patient had a single, tumor-like enhancing lesion associated with extensive vasogenic edema on MR imaging. Conversely, PACNS presenting multiple lesions that also mimic aggressive multifocal cerebral neoplasm have been reported (26, 3134). A retrospective study of 10 tumor-like PACNS cases in France found that the number of patients with single and multiple lesions was similar (4 and 3 patients, respectively) (35).…”
Section: Discussionmentioning
confidence: 99%
“…Though uncommon in the pediatric population, there are reports in adults of histiocytic disorders leading to CNS vasculitis (Table 1) [9-10]. Vasculitides in children is a rare condition as a whole, occurring in no more than 53 in 100,000 (12401245, 15517648).…”
Section: Discussionmentioning
confidence: 99%
“…A beaded appearance of the cerebral arteries seen on angiography might be a most supportive feature for vasculitis, reflecting variable degrees of stenosis or occlusion, however, these findings are rarely evident in PACNS. The PACNS showing tumor‐like images with mass effect are rare but have been reported, which usually show T2 high, heterogeneously enhancing lesions . Those previously reported mass‐forming PACNS cases were summarized in Table .…”
Section: Discussionmentioning
confidence: 99%